BER analysis of amplify-and-forward relaying FSO systems using APD receiver over strong atmospheric turbulence channels - Duong Huu Ai; Van Loi Nguyen (Institute of Advanced Engineering and Science, 2019)
In this paper, we theoretically analyze the performance of amplify-and-forward (AF) serial relaying free-space optical (FSO) systems using avalanche photodiodes (APD) and subcarrier quadrature amplitude modulation (SC-QAM) over strong atmospheric turbulence channels modelled by gamma-gamma distribution. Closed-form expression for average bit error rate (BER) of system is theoretically derived talking into account APD shot noise, thermal noise as well as the impact of atmospheric loss and turbulence. The numerical results show that using AF relay stations can extend the transmission distance and help to improve performance of FSO system significantly when compared with the direct transmission. Moreover, the selection of APD gain value is indispensable to the system performance. The proposed system could be achieved the best performance by selecting an optimal APD gain value. In addition, the optimal value of APD gain also significantly depends on various conditions, such as link distance, the number of relay stations and APD receiver noise.